Identifikasi Potensi Akuifer Tertekan berdasarkan Data Resistivitas Batuan (Kasus : Kecamatan Sambirejo Kabupaten Sragen): Darsono, Budi Legowo, Darmanto - Darsono Darsono; Budi Legowo Budi Legowo; Darmanto Darmanto (Jurnal Fisika dan Aplikasinya, 2017)
Confined Aquifer identification in Sambirejo District using Geoelectric resistivity methods with Schlumbeger. array. The measurement were performed by using a resistvitymeter OYO McOHM-el model 2119C with a length of current electrode is 350 meters. survey location in Sambirejo Distric with five geolistrik point i.e TS1(Sidoharjo, Musuk), TS2 (Gempol), TS3 (Sambirejo), TS4 (Dagangan, Blimbing) dan TS5 (Sidorejo, Blimbing). The data processing used IP2win software version 3.1.2c. The research is to identify of litology, depth and thick layer with confined aquifer potention at the research area. The result shows that litology of aquifer layers were detected i.e. clayed sands, sands, gravel sands dan breccia. The depth of confined aquifer detect between 23.95 meters to > 168,3 meters and layers thick between 39,6 meters to 98.4 meters. The Confined aquifer have big groundwater source i.e. TS1, TS4 and TS5.